Enhancing the teaching quality of part-time faculty in a Jamaican adult education institution: (with a focus on continuing professional development) - Dawkins, Yvonne (2011)
Typically, adult educators in Jamaica are part-time employees who are either trained in pedagogy or are employed because of their advanced training or skills in a particular discipline. As adult education in Jamaica and the Caribbean undergoes change, policy focus has concentrated on identifying the discipline with lifelong learning rather than adult literacy. Although the importance of the role of adult educators to the change process is acknowledged, the changes in adult education are not yet focussed on the role of the adult educator and equipping the adult educator to function in this dynamic environment.